Modeling the OCL Standard Library - Willink, Edward (Electronic Communications of the EASST, 2011)
OCL is widely used by UML and other languages to constrain meta-models and perform evaluations on models. The OCL specification is the result of diligent but time-constrained human endeavor and so contains many inconsistencies, most of which are relatively easy to ignore as obvious typographical mistakes. However the need to ignore minor discrepancies undermines rigorous treatment of more significant issues. The minor issues can be substantially eliminated by auto-generating the specification. This paper provides early community visibility of proposed solutions to a variety of issues that arose while developing a model for the OCL Standard Library that forms the core of the OCL specification.